Haptic gait retraining for knee osteoarthritis treatment - Shull, Pete; Lurie, Kristen; Mihye Shin; Besier, Thor; Cutkosky, Mark (2010 IEEE Haptics Symposium, 2010)
In this paper we introduce haptic gait retraining as a new method for treating early stage medial compartment knee osteoarthritis and for reducing risk of the disease in individuals who may be susceptible. The hardware and software for implementation are presented including rotational skin stretch and vibration haptic devices used to inform subjects of alterations in gait movements. We also present a method based on real-time motion analysis for predicting new subject-specific gaits tailored to change knee joint loading. This approach uses correlation data between gait parameters and knee loading as well as a localized linearization technique to compute a final combined-parameter gait with minimum change from the subject's original, unaltered gait. Finally, we validate the haptic gait retraining system with a user experiment and show that, for the duration of the experiment, the user is able to positively change knee joint loading to approximately the same degree as HTO surgery.